Changes in biochemical parameters in rabbits blood after combined treatment of eimeriosis - N. V. Bogach; L. A. Franchuk (Российский паразитологический журнал, 2016)
Immunosuppressive effect of brovitacoccid in combination with probiotic Baikal EM 1U during spontaneous infection of rabbits caused by Eimeria stiedae, E. magna, E. perforans, E. media is studied. Brovitacoccid with probiotic Baikal EM 1U less exhibits immunosuppressive effect than separately brovitacoccid. The combined use of brovitacoccid with probiotic leads to increased levels of γ-globulins, which indicates an increase of immunological reactivity of rabbits.